Association of metabolic dysfunction-associated steatotic liver disease with bone health in adults: a systematic review and meta-analysis of observational studies - Li, Xingzhi; Luo, Wei; Chen, Ke; Peng, Yong (Frontiers in Endocrinology, 2026)
BackgroundSeveral studies have explored the effects of metabolic dysfunction-associated steatotic liver disease (MASLD) on bone mineral density (BMD) and bone turnover markers (BTMs) in adults and the risk of osteoporotic fractures. However, the extent of adverse effects of MASLD on bone health remains uncertain. This systematic review and meta-analysis aimed to investigate the effects of MASLD on bone health in adults.MethodsWe searched PubMed, Medline, EMBASE, Cochrane Library, and Scopus for observational studies published from inception to June 2025 that reported MASLD effects on bone health.ResultsThis meta-analysis indicated that MASLD was associated with increased femur BMD (WMD: 0.03 g/cm2, 95% CI: 0.02 to 0.03, P<0.001), especially in women (WMD: 0.02 g/cm2, 95% CI: 0.01 to 0.04, P = 0.002) and overweight people (WMD: 0.04 g/cm2, 95% CI: 0.01 to 0.06, P = 0.002). MASLD was also significantly associated with increased osteoporosis/osteoporotic fractures (OR: 1.23, 95% CI: 1.13-1.34; P<0.001) and decreased BTMs (CTX: WMD: -0.03 ng/mL, 95% CI: -0.05 to -0.02, P<0.001; OC: WMD: -1.86 ng/mL, 95% CI: -2.69 to -1.03, P<0.001; P1NP: WMD: -4.59 ng/mL, 95% CI: -5.64 to -3.54, P<0.001).ConclusionsMASLD was significantly associated with increased femur BMD compared to non-MASLD patients, especially in women and overweight individuals. Interestingly, increased risk of OP/osteoporotic fractures and decreased BTMs were significantly associated with MASLD. This may suggest that BMD underestimates the risk of OP/osteoporotic fractures in MASLD patients.